O desafio da inclusão de alunos com NEE em aulas de matemática: o caso dos anos iniciais do ensino fundamental - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
This research aimed to contributing to the investigations about the Inclusion-Mathematics relations, prioritizing the inclusive and pedagogical aspects of this relationship, by means of the elaboration of an explanatory booklet and of orientation directed to the teachers who teach Mathematics. Restrictedly, because it is a Professional Master's Degree, it aimed to develop an orientation book for teachers, making them aware of the possibility and necessity of including students with SEN in Mathematics classes. The study was developed in a public school in the Federal District and the Multidimensional Scale of Inclusion of Students with SEN in Mathematics Classes as well as observations made in the classroom was used as a research tool. As a result of the investigations, a Teacher Orientation Booklet was prepared that teaches Mathematics to Students with SEN, which was made public through a lecture given by Professor Geraldo Eustaquio Moreira. The main results have shown that although the issue of special needs education is old, there is still much to be done; That the difficulties encountered by teachers who teach mathematics for pupils with SEN are enormous, despite the great progress that has been made in the last decades; That the training of teachers who teach mathematics is insufficient, considering the readiness to deal with students with SEN; That many teachers who teach mathematics, in general, are resistant to inclusion in their classrooms; That continuing education needs to be an instrument capable of assisting teachers in the health processes of their difficulties with the subject; That Inclusive Mathematics Education is recent and still seeks a place in the academic world; That the reception of the Orientation Booklet for Teachers Teaching Math to Students with SEN by the teachers was very positive, among others. The results suggested a set of questions that can be approached in future investigations, involving the initial formation of the teachers who teach Mathematics; The educational resources available in schools to deal with students with SEN; The inclusion of these students in exact disciplines, among others.
Keywords: Necessidades Educativas Especiais; Educação Matemática Inclusiva; Inclusão; Cartilha de conscientização; Special Educational Needs; Inclusive Mathematics Education; Inclusion; Awareness booklet; TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL